Effect of end-groups on simultaneous oleophobicity/hydrophilicity and anti-fogging performance of nanometer-thick perfluoropolyethers (PFPEs)1. Issue 39 (2nd May 2015) - Wang, Yongjin; Knapp, James; Legere, Aleigh; Raney, Jacob; Li, Lei
<x xml:space="preserve">Abstract</x> Simultaneously oleophobic/hydrophilic coatings are highly desirable in many important applications, e.g., anti-fogging.